Redesigning Food Packaging Using Kansei Engineering Method : Case Study at Griya Produksi SME - Hapsoro Agung Jatmiko; Afan Kurniawan; Rizki Ma’arif (Jurnal Ilmiah Teknik Industri, 2023)
Food Packaging plays an important role in food industry, as it is not only to protect the food within, but also as a mean of advertisement for the product, a good packaging more or less could improve the awareness of the people to buy more the product. Eggroll Sasha by Griya Produksi SME is one of its best product. Made from sweet potato, the product is known for its taste, but unfortunately the packaging does not represent the taste of the product. Using Kansei Engineering (KE), the current packaging is being redesigned in order to elevate the aesthetics and to inform the customer about the existence of the product. The respondent of this research are people who reside in 3 district around Griya Produksi’s Factory, and the one who already purchase or eaten the product. The output of this research is the brand new redesigned package for the eggroll